2010
DOI: 10.1080/14789940903564388
|View full text |Cite
|
Sign up to set email alerts
|

Murder by numbers: monetary costs imposed by a sample of homicide offenders

Abstract: Prior research on the monetary costs of criminal careers has neglected to focus on homicide offenders and tended to minimize the public costs associated with crime. Drawing on expanded monetization estimates produced by Cohen and Piquero, this study assessed the monetary costs for five crimes (murder, rape, armed robbery, aggravated assault, and burglary) imposed by a sample of (n ¼ 654) convicted and incarcerated murderers. The average cost per murder exceeded $17.25 million and the average murderer in the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(96 citation statements)
references
References 36 publications
(46 reference statements)
0
95
0
1
Order By: Relevance
“…Wykorzystywanie seksualne wpływa nie tylko na stan mentalny i psychologiczny ofiary, ale także na jej funkcjonowanie fizyczne, społeczne i ekonomiczne oraz jej relacje interpersonalne [8]. Jeśli chodzi o skutki ekonomiczne tego zjawiska, badania przeprowadzo ne w Stanach Zjednoczonych wykazały, że udzielenie jednej ofierze zgwałcenia pomocy lekarskiej i prawnej w odpowiednich placówkach oznacza dla jednostki i społeczeństwa roczny koszt w wysokości ok. 151 423 dolarów [9]. Pod względem psychologicznym i spo łecznym oraz w obszarze relacji interpersonalnych skutki zgwałcenia ujawniają się w trzech wymiarach.…”
Section: Wstępunclassified
See 1 more Smart Citation
“…Wykorzystywanie seksualne wpływa nie tylko na stan mentalny i psychologiczny ofiary, ale także na jej funkcjonowanie fizyczne, społeczne i ekonomiczne oraz jej relacje interpersonalne [8]. Jeśli chodzi o skutki ekonomiczne tego zjawiska, badania przeprowadzo ne w Stanach Zjednoczonych wykazały, że udzielenie jednej ofierze zgwałcenia pomocy lekarskiej i prawnej w odpowiednich placówkach oznacza dla jednostki i społeczeństwa roczny koszt w wysokości ok. 151 423 dolarów [9]. Pod względem psychologicznym i spo łecznym oraz w obszarze relacji interpersonalnych skutki zgwałcenia ujawniają się w trzech wymiarach.…”
Section: Wstępunclassified
“…Sexual abuse not only affects the victim's mental and psychological dimension but also the physical, social, economic dimensions and interpersonal relationship [8]. In relation to the economic consequences of this problem, studies in the United States showed that referral of each rape victim to the legal and medi cal centers imposed an expense about 151,423 dol lar on the individual and society every year [9]. In terms of the psychological, social dimension and interpersonal relationships, the consequences of a sexual assault is revealed in three states of short term complications such as severe fear and anxi ety, longterm complications such as decrease of selfesteem, selfblame and feeling guilty and post traumatic stress disorder [8].…”
Section: Introductionmentioning
confidence: 99%
“…Violent crime, much of which is preventable, is extremely costly: The cost of dealing with a murder is typically about $17.5 million, a rape $448,532, a robbery $335,733, an aggravated assault $145,379, and a burglary $41,288 (DeLisi et al, 2010). These costs are staggering and cannot be ignored.…”
Section: Figure 4: Proportion Of Accused Youth Cleared By Means Othermentioning
confidence: 99%
“…violence can lead to costs of more than US$17 million per offense (DeLisi et al, 2010). However, if prison violence cannot be reduced by making it a more unpleasant living environment, the most attractive cost reduction factor has been missed out.…”
Section: International Journal Of Offender Therapy and Comparative Crmentioning
confidence: 99%